2020
DOI: 10.1161/strokeaha.120.029494
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Unexplained Early Neurological Deterioration After Endovascular Treatment for Acute Ischemic Stroke

Abstract: Background and Purpose: Although the efficacy of endovascular treatment (EVT) in patients with anterior circulation ischemic stroke (AIS) is well documented, early neurological deterioration after EVT remains a serious issue associated with poor outcome. Besides obvious causes, such as lack of reperfusion, procedural complications, or parenchymal hemorrhage, early neurological deterioration may remain unexplained (UnEND). Our aim was to investigate predictors of UnEND after EVT in patients with AIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 41 publications
6
52
3
Order By: Relevance
“…All the patients were treated with EVT, 131 patients (62.1%) received additional intravenous thrombolysis. The median NIHSS score on admission was 14 in both groups, whereas the median 24-h NIHSS score differed significantly, with 32 (IQR:22-33) in the END group versus 6 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) in the group without END. Figure 1 illustrates the course of the NIHSS score between the baseline and 24 h of all the patients.…”
Section: Patient Characteristicsmentioning
confidence: 87%
See 4 more Smart Citations
“…All the patients were treated with EVT, 131 patients (62.1%) received additional intravenous thrombolysis. The median NIHSS score on admission was 14 in both groups, whereas the median 24-h NIHSS score differed significantly, with 32 (IQR:22-33) in the END group versus 6 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) in the group without END. Figure 1 illustrates the course of the NIHSS score between the baseline and 24 h of all the patients.…”
Section: Patient Characteristicsmentioning
confidence: 87%
“…To date, only a few studies have investigated END after EVT with varying incidence rates and predictors of END due to different definition and inclusion criteria [ 5 , 8 , 10 ]. Girot et al, who focused on unEND, mainly found nonmodifiable factors such as premorbid disability (mRS ≥ 2), age and diabetes mellitus as predictors for neurologic deterioration; however, baseline imaging parameters were not included in the analysis and only cases with favorable reperfusion status and no early complications were considered as END, which limits the comparability with our results [ 5 ]. Kim et al and Zhang et al identified the recanalization status as the most important predictor [ 8 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations